Discovering the Unhidden: Heidegger's Interpretation of Plato's Allegory of the Cave and its Implications for Psychotherapy (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
This paper explores Heidegger’s interpretation of Plato’s Allegory of the cave from Politeia. Unlike Plato, Heidegger sees the essence of truth as a way of being and not an object. This perspective I believe, allows us to see the allegory as a metaphor for the process in therapy. Reference to one particular therapy session is an attempt to demonstrate how an exploration between therapist and client, in the mode of authentic disclosedness, can enable the truth about existence to be uncovered or disclosed. What is to be disclosed Heidegger terms as the unhidden. But t he que stion i s w hat t ruth i tself i s. The first s tep to wards understanding this question is the insight that man comes to himself, and f inds t he g round of hi s D asein, i n t hat e vent of de concealment which constitutes the unhiddenness of beings. (Heidegger 1988:55) Key words Unhidden; Hidden; Authentic disclosedness; Liberation. ‘Behind’ t he ph enomena of phenomenology t here i s essentially nothing else; on the other hand, what is to become a phenomenon can be hidden (Heidegger 1969:60)
Keywords: Unhidden; Hidden; Authentic disclosedness; Liberation